2009
DOI: 10.2131/jts.34.s111
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative work on evaluation of ovarian toxicity 10) Two- or four-week repeated dose studies and fertility study of di-(2-ethylhexyl) phthalate (DEHP) in female rats

Abstract: INTRODUCTIONAs part of a collaborative study on toxicity related to female fertility, we performed experiments using di-(2-ethylhexyl) phthalate (DEHP), widely used as a plasticizer of polyvinyl chloride (PVC) and a known peroxisome proliferator (Lake et al., 1987), liver carcinogen (Reddy and Lalwai, 1983) and ovarian toxicant in rodents (Davis et al., 1994). Short-term exposure to DEHP resulted in hypoestrogenic anovulatory cycles and polycystic ovaries in adult rats (Davis et al., 1994). Longterm exposure t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 13 publications
0
24
1
Order By: Relevance
“…These studies have observed effects of DEHP exposure such as reduced anogenital distance, reduced testes weights, reduced testosterone production [17, 25], delayed pubertal onset, and abnormal seminiferous tubule formation [26]. A few studies have examined the effects of exposure to DEHP on female reproduction [28, 33-35]. These studies have shown that DEHP exposure causes a decline in pregnancy rates and irregular estrous cyclicities at very high doses [33], decreased overall fertility [34], atresia of tertiary follicles in adult rats, and delayed onset of puberty [35].…”
Section: Discussionmentioning
confidence: 99%
“…These studies have observed effects of DEHP exposure such as reduced anogenital distance, reduced testes weights, reduced testosterone production [17, 25], delayed pubertal onset, and abnormal seminiferous tubule formation [26]. A few studies have examined the effects of exposure to DEHP on female reproduction [28, 33-35]. These studies have shown that DEHP exposure causes a decline in pregnancy rates and irregular estrous cyclicities at very high doses [33], decreased overall fertility [34], atresia of tertiary follicles in adult rats, and delayed onset of puberty [35].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, it is virtually impossible to avoid chronic low-level exposure to phthalates. It is of note that MEHP, a metabolite of DEHP, which has been reported to lead to oocyte atresia (Takai et al 2009), suppresses oestradiol (E 2 ) synthesis and ovulation in female rats. In addition, MEHP leads to a reduced size of pre-ovulatory follicles and suppresses follicular development when cultured in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…Females with chronic and long-term exposure to high levels of DEHP are especially prone to negative reproductive outcomes, i.e., low pregnancy and high miscarriage rates [9,10], irregular estrogen and progesterone levels with no ovulation [11,12], and pregnancy complications such as anemia, hypertensive disorders and pre-eclampsia [13]. Although DEHP apparently compromises pregnancy outcomes in female, the underlying mechanism is still unclear.…”
Section: Introductionmentioning
confidence: 99%